Risky Business: Transactional Rhetoric in José Penso de la Vega (ca. 1650-1692) - Armon, Shifra (Revista Canadiense de Estudios Hispánicos, 2023)
José Penso de la Vega (ca. 1650-1692) was a Sephardic businessman and writer in Amsterdam. His exuberant prose and historical significance are on display in his dialogized guide to the Dutch stock exchange, Confusión de confusiones (1688), and in the novel collection, Rumbos peligrosos (1683). Uniting these disparate texts is their attention to transactions, whether affective or financial. In both cases, Penso’s narratives anatomize the risk-taking and risk-avoidance tactics required to stay afloat in the speculative marketplaces of courtship and investment.